Variables Affecting Financial Inclusion. Case Study Colombia - Valencia-Arias, Alejandro; Pacheco, Diana; Cardona Valencia, Daniel (Rev. Téc. Fac. Ing. Univ. Zulia, 2023)
Financial inclusion has been related exclusively to banking penetration, affirming that the use of the financial system expands savings and development. In this sense, this study analyzed the impact of certain socioeconomic and banking penetration variables on savings formation, using information from the Global Findex database and applying a binary logistic regression analysis, as well as a neural network study. The regression showed high significance and correlation between savings and the inclusion variable, while the network was able to estimate 83.2 % of the cases as correct, with relevance in variables such as loan and education level. These results indicate that variables such as education and income level have a positive impact on savings, while the generation of credit acts as an inhibitor of savings; once there are high-rate differentials and the loans are mostly for consumption with low direction to investment